UPAYA MENANAMKAN PEMAHAMAN PERKEMBANGAN ANAK PADA ORANGTUA DALAM MENINGKATKAN KETAHANAN KELUARGA DI TENGAH WABAH PANDEMI COVID-19 - Sintia Nirdiawati; Nandang Rukanda; Dewi Safitri Elsap (Comm-Edu (Community Education Journal), 2023)
AbstractThis research is motivated by the occurrence of a pandemic in Indonesia, known as Covid-19 which has spread to Indonesian citizens, so the government appeals to always maintain health and pay attention to child development properly. The purpose of this study is (1) to determine the process of understanding the development of children in parents in the midst of the Covid-19 pandemic. (2) To know the process of instilling an understanding of child development in parents in the midst of the Covid-19 pandemic outbreak. (3) To find out the inhibiting factors in efforts to instill an understanding of child development in parents in increasing family resilience in the midst of the Covid-19 pandemic outbreak. The method used is a qualitative approach with a descriptive method. Data collection techniques used in this study were observation, interviews and documentation studies. The location of the research was carried out in Cimalik Village, RT 06 RW 03, Karanganyar Village, Cililin District, West Bandung Regency. The subjects of the research were one head of the BKB cadre (Bina Keluarga Toddler) and 15 parents who had early childhood from the management and members of BKB. The results showed that the efforts to instill an understanding of child development in parents in increasing family resilience were going well. The program activities must continue to run on an ongoing basis and be evaluated in stages in order to create program goals in improving the quality of the population in Cimalik Village. Keywords: Child Development, Familiy Resilience, Familiy Resilience Factor